Implementasi Algoritma Apriori Pada Sistem Persediaan Stok Obat - Akhiruddin Pulungan; Billy Hendrik (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
As a fairly large institution, management and system development that needs to be designed from a manual basis to a digital basis is very necessary, of course, so that the use of Technology and Information can also be applied to minimize deficiencies and bring the expected profits in providing medicine stock at Islamic boarding school clinics. Due to geographic location, it is necessary to develop a system that can assist in handling the availability of drug stocks so that the process of distributing drugs to patients can run without problems. It is hoped that the use of the Apriori algorithm can help in supplying medicine stock at the Darul Mursyid Islamic boarding school.